Liberation of the Oppressed in Madurese Manuscripts Kitab Maksiat; A Study of Liberation Theology - Chair, Badrul Munir (The Faculty of Ushuluddin and Humanities, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2023)
The daily life of the Muslim community today is faced with various humanitarian problems, including economic problems and oppression. These problems must be solved immediately by reinterpreting the sources of Islamic theology with humanitarian goals. In order for theology to be present in solving various problems experienced by modern humans, it is necessary to reinterpret the values contained in Islamic teachings, from being solely theocentric to theo-anthropocentric. This research will elaborate on the liberation of the tertin das in the manuscript of Kitab Maksiat found in Madura. This type of research is a literature research. This research uses a qualitative approach. The main source of this research is Kitab Maksiat, which is a 24-page Arabic manuscript written in prose style. The results of this study can be concluded that the concept of liberation in the manuscript of Kitab Maksiat can be described into two categories, namely liberation from exploitative economic structures, and liberation of the oppressed (mustad'afin). The attitude of liberation from degrading fellow human beings in the manuscript is manifested in not prioritising the rich over the poor, siding and respecting the mustad'afin, that wealth is not a measure to determine who should be prioritised.